Advances and challenges of membrane–protein complex production. (June 2015) - Zorman, Sarah; Botte, Mathieu; Jiang, Qiyang; Collinson, Ian; Schaffitzel, Christiane
Highlights: Membrane–proteins exist in complexes. The appropriate expression host is key to produce membrane–proteins. Designed bacterial strains and baculovirus-insect cell expression are successfully used. Mild detergents, amphipols and nanodiscs are stabilizing membrane–proteins. Cryo-EM can achieve high-resolution for scarce complexes extracted from source. Abstract : Most membrane–proteins exist in complexes rather than isolated entities. To fully understand their biological function it is essential to study the intact membrane–protein assemblies. The overexpression and purification of many essential membrane–protein complexes is still a considerable and often unsurmountable challenge. In these cases, extraction from source is the only option for many large multi-subunit cellular machines. Here, we describe recent advances in overexpression of multi-subunit membrane–protein complexes, the strategies to stabilize these complexes and highlight major achievements in membrane–protein structural research that were facilitated by the prospect of achieving subnanometer to near-atomic resolution by electron cryo-microscopy.